A DESCRIPTIVE STUDY ON THE USE OF FIGURATIVE LANGUAGE IN ENGLISH SONG LYRICS BY WESTERN MUSICIANS - Marzuki, Ismail (2007)
This research is conducted in the objective to observe and to describe the use of figurative language in English song lyrics by western musicians and the meaning. As it is assumed that song lyrics are one of several human's creativities in communicating all of what has kept in their mind through the medium of language use. This research takes the English song lyrics especially written by western musicians as the object of the study. Furthermore, the data for this research is figurative language taken from the English song lyrics written by western musicians. Hence two major problems proposed, which are: (1) what are the types of figurative language used by western musicians in English song lyrics, (2) what are the meanings of figurative language used in English song lyrics by western musicians. In collecting the data, the writer applies the observation and documentation by studying carefully the English song lyrics written by western musicians. And then classifies the data based on the Perrine's Lawrence theory of figurative language and other scientists that support it. Whereas, in order to elaborate behind the meaning of figurative language utterance in English song lyrics written by western musicians, the writer applies the Leech's theory of meaning and the Levinson's theory of speech act and other scientist's theories that support it. The result of the study indicates that in English song lyrics, western musicians use figurative language dominated by metaphor as their creativity of mind expressions. Besides, the writer also finds other type of figurative language namely; personification, apostrophe, hyperbole, metonymy, irony, symbol and simile. Closely related to the meaning of figurative language in English song lyrics by western musicians, here the writer finds that figuratively western musicians try to convey sharply, meaningfully, ha ve a power, varitype, assertive of their ideas, meaning, feeling, truth, love, imagination expression by taking an object include abstract, concrete, death and live illustrated as they are compared implicitly or explicitly, or by making an overstatement. In addition it is the selfway of the western musician in giving the audience an imaginative pleasure and giving the extra dimension to the language of their mind expression through the song lyrics.